STUDY OF ISLAMIC LEGAL PHILOSOPHY AS A PHILOSOPHICAL APPROACH TO ISLAMIC LAW - Sri Ayu Andari Putri Alwaris; Achmad Musyahid; Rahmatiah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Philosophy can be interpreted as love or a tendency towards wisdom. The philosophy of Islamic law is a philosophical study of the nature of Islamic law, the source of the origin of Islamic law and the principles of its application as well as the function and benefits of Islamic law for the lives of the people who implement it. The urgency of the philosophy of Islamic law is to make philosophy an approach in exploring the nature, sources and objectives of Islamic law. Positioning the philosophy of Islamic law as one of the important fields of study in understanding the sources of Islamic law which come from revelation and the results of ijtihad of scholars. The philosophy of Islamic law has an important role in the development of Ijtihad.